2021
DOI: 10.3390/nano11020536
|View full text |Cite
|
Sign up to set email alerts
|

A Review on LDH-Smart Functionalization of Anodic Films of Mg Alloys

Abstract: This review presents an overview of the recent developments in the synthesis of layered double hydroxide (LDH) on the anodized films of Mg alloys prepared by either conventional anodizing or plasma electrolytic oxidation (PEO) and the applications of the formed composite ceramics as smart chloride traps in corrosive environments. In this work, the main fabrication approaches including co-precipitation, in situ hydrothermal, and an anion exchange reaction are outlined. The unique structure of LDH nanocontainers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 113 publications
0
9
0
Order By: Relevance
“…Consequently, Mg–Gd alloys shows better long-term degradation performance compared to anodized AZ31 Mg alloy. Since, anodic oxidation coatings singularly cannot full fill diverse clinical demands several studies reported their combination with chemical conversion [ 174 , 175 ], electrodeposition [ 176 ], LDHs [ 177 ], sol-gel [ 178 ] coating techniques. These coatings exhibit promising improvement in corrosion resistance and bioactivity of Mg alloys.…”
Section: Coatings and Their Current Statusmentioning
confidence: 99%
“…Consequently, Mg–Gd alloys shows better long-term degradation performance compared to anodized AZ31 Mg alloy. Since, anodic oxidation coatings singularly cannot full fill diverse clinical demands several studies reported their combination with chemical conversion [ 174 , 175 ], electrodeposition [ 176 ], LDHs [ 177 ], sol-gel [ 178 ] coating techniques. These coatings exhibit promising improvement in corrosion resistance and bioactivity of Mg alloys.…”
Section: Coatings and Their Current Statusmentioning
confidence: 99%
“…The first directly grown LDH on PEO of Mg alloys without autoclave was achieved by Petrova et al [ 290 ]. Currently, LDH post-treatment is being successfully exploited for the fabrication of composite PEO/inhibitor-loaded LDH coatings on Mg alloys in an increasing number of works [ 291 , 292 , 293 , 294 , 295 , 296 , 297 ]. Chen et al investigated PEO/LDH systems with a variety of cations in the LDH layer, such as Ni-LDH, Zn-LDH, Al-LDH, and MgFe-LDH [ 294 , 295 ], of which Ni-LDH was found to form a continuous LDH layer over the PEO surface and produce an order of magnitude increase in total impedance (up to 5 × 10 5 Ωcm 2 ) compared with a stand-alone PEO coating.…”
Section: Post-treatmentmentioning
confidence: 99%
“…Micro arc oxidation (MAO) refers to a novel technology for in-situ growth of ceramic oxide film on an Mg alloy, and the formed MAO coating shows a rough microstructure and is firmed to Mg substrate [ 35 , 36 , 37 ]. MAO can significantly improve the corrosion resistance of Mg alloy substrates.…”
Section: Superhydrophobic Coatingsmentioning
confidence: 99%